Testing Antioxidant Activity of Plumeria Alba and Plumeria Rubra Ethanolic Extracts Using DPPH and Frap Methods and Determining Their Total Flavonoid and Phenolic Levels - Muhtadi Muhtadi; Aulia Ayu Fatkhurrohmah Wiyono (Journal of Nutraceuticals and Herbal Medicine, 2020)
Plumeria sp. or Frangipani with local name; Kamboja plants have been reported to have antimicrobial, anticancer, and antioxidant activities spread in every part of the plant. Previous studies that have been carried out only reported antioxidant activity in certain parts with certain methods. This study compared the most potent antioxidant activity in several parts of the plant with different methods with statistically significantly different results. This study aims to determine the antioxidant activity of Plumeria alba L. and Plumeria rubra L. by DPPH and FRAP methods and to determine the total flavonoid and phenolic levels. The methods used are two different methods, namely the DPPH and FRAP methods. Antioxidant activity test using the DPPH method showed that the highest antioxidant activity was found in P. rubra flowers with an IC50 value of 150, 20 ppm while in the FRAP method the highest activity was in P. rubra leaves with an antioxidant activity value of 79.75 mg AAE / g extract. The highest flavonoid content was found in the sample extract of P. rubra leaves with 117.83 mg quercetin equivalent/g extract, while the highest total phenolic content was found in P. rubra flowers with 108.85 mg gallic acid equivalent/g extract. The results showed that the highest antioxidant activity using the method DPPH correlated with phenolic content while the FRAP method correlated with flavonoid content. Antioxidant activity in P. rubra leaves comes from flavonoid compounds while in P. rubra flowers come from phenolic compounds. So that each plant sample can have a source of antioxidant activity from different compounds.